High-fat diet and neuroinflammation: The role of mitochondria - Mingxue Song; Yao Bai; Fuyong Song (Pharmacological Research, 2025)
In recent years, increasing evidence has supported that high-fat diet (HFD) can induce the chronic, low-grade neuroinflammation in the brain, which is closely associated with the impairment of cognitive function. As the key organelles responsible for energy metabolism in the cell, mitochondria are believed to involved in the pathogenesis of a variety of neurological disorders. This review summarizes the current progress in the field of the relationship between HFD exposure and neurodegenerative diseases, and outline the major routines of HFD induced neuroinflammation and its pathological significance in the pathogenesis of neurodegenerative diseases. Furthermore, the article highlights the pivotal role of mitochondrial dysfunction in driving the neuroinflammation in the setting of HFD. Danger-associated molecular patterns (DAMPs) from damaged mitochondria can activate innate immune signaling pathways, while mitochondrial dysfunction itself can lead to metabolic remodeling of inflammatory cells, thus inducing neuroinflammation. More importantly, mitochondrial damage, neuroinflammation, and insulin resistance caused by HFD form a mutually reinforcing vicious cycle, ultimately leading to the death of neurons and promoting the progression of neurodegenerative diseases. Thus, in-depth elucidation of the role and underlying mechanisms of mitochondrial dysfunction in HFD-induced metabolic disorders may not only expand our understanding of the mechanistic linkages between HFD and etiology of neurodegenerative diseases, but also help develop the specific strategies for the prevention and treatment of neurodegenerative diseases.